The Role of Increasing Indonesian Literacy in Building Effective Communication Skills in the Digital Era - Febriana, Chintiya; Fikri, Hasnul (Jurnal Pendidikan Indonesia, 2024)
In the current 4.0 revolution, the digitalization of information and communication which continues to develop massively and dynamically is both an opportunity and a challenge in empowering Indonesia's young generation as national assets. Digital technology is widespread, but not yet used effectively and meaningfully. Misuse of digital technology can occur and can endanger all aspects of life. As a result, digital literacy needs to be improved in every aspect of life, especially in the field of education. Digital education has great potential to increase digital literacy as a means of improving reading and writing skills. Apart from that, digital literacy plays an active role in strengthening national identity through mastery of science and technology and extensive use of the Indonesian language. Digital literacy refers to the knowledge and skills of using digital media to obtain information and express ideas in a legitimate way. Therefore, digital literacy must be used and incorporated into the learning process. The goal of learning Indonesian in schools and the National Literacy Movement is to be fully achieved because the use of digital literacy will enable creative, innovative and fun learning innovations. The purpose of this article is to discuss the role of literacy in learning Indonesian in the digital era. This article discusses how the development of literacy skills in Indonesian language learning changes with the development of digital technology. In addition, the main challenges in building effective literacy skills when learning Indonesian in the digital era are also discussed. This article also explores how the role of literacy in Indonesian language learning impacts students' reading, writing and critical thinking abilities in the digital era.